Identifying Hail Events Using Weather Radar and Satellite Data (Study Case in East Java on 23 December 2021) - Arif Krisna Widadi; Maulana Sunu Pratama (West Science Nature and Technology, 2023)
Hail is an extreme weather phenomenon that rarely occurs in tropical regions such as Indonesia. However, if convective clouds are strong enough to develop higher, a hail event is likely to occur. Interestingly, on 23 December 2021, hail events occurred in four different nearby locations. Weather Radar data from the Juanda Meteorological Station and Himawari-8 Satellite data were used to analyse this hail phenomenon. The Radar measured reflectivity values, cloud top height, water vapour content, and the derivative product of the probability of hail occurrence. The Himawari-8 data were utilised to observe cloud top temperatures. From the results, it is known that the reflectivity value of hail is in the range of 45 dBZ to 55 dBZ, with a probability of hail above 80%, and the temperature at the top of the Cumulonimbus cloud is between -67.5°C to -82.5°C. These thresholds may be used in monitoring hail events, especially in the East Java region.